An ethnozoological investigation at tropical wildlife forest areas located in Araku, Jangareedy Gudem and Mylavaram Forests of Andhra Pradesh - Anthumary Kondaveeti,; Dr. Manoj Singh, (The Bioscan, 2024)
The present study examines the ethnozoological techniques employed by the Bagata, Gadaba, Koya, Savara of Araku; Kondareddies, Kondakammara, Konda Dora, Kondakapu, Valmiki of Jangareedy Gudem; Yerukula, Dabba Yerukula , Nakkala, Sugalis, Koya Mukha Doras, Yenadis, Lambadis, Chenchus, Lambadi Banjaras of Mylavaram Forests of Andhra Pradesh, specifically focusing on the utilization of various animal products and their derivatives for medicinal purposes. This study aims to provide a comprehensive understanding of the utilization of 23 animal species, which have been identified as folk medicine within the local tribal population. A field survey was undertaken, using interviews and a standardized questionnaire, which unveiled the utilization of 23 species for the treatment of several ailments. The zootherapeutic expertise that has been passed down through generations primarily relies on the utilization of domestic and wild animals as significant sources of medicinal substances. It is recommended that this type of information might be valuable in preserving life during emergencies. The report also highlights the ways for conserving and managing faunistic resources. The ethnozoological practice emphasizes the necessity of enhancing traditional knowledge of zootherapy in order to explore new avenues in pharmaceutics.